High-Resolution Side Channels for Untrusted Operating Systems - Hähnel, Marcus; Cui, Weidong; Peinado, Marcus (2017 USENIX Annual Technical Conference (ATC'17), 2017)
Feature-rich mass-market operating systems have large trusted computing bases (TCBs) and a long history of vulnerabilities. Systems like Overshadow, InkTag or Haven attempt to remove the operating system (OS) from the TCB of applications while retaining its functionality. However, the untrusted OS's control of most physical resources puts it in a much better position to launch side-channel attacks than traditional unprivileged side-channel attackers. Initial attacks focused on the page-fault channel, demonstrating significant information leakage for three legacy applications. We present two new side channels for an untrusted OS which use timer interrupts and cache misses to achieve higher temporal and spatial resolution than the page-fault channel. We leverage the untrusted OS's control over hardware to reduce noise in the side channels to enable successful attacks in just a single run of the target. We demonstrate that our side channels enable attacks against new SGX applications such as VC3 that were designed not to trust the OS. We also show a new attack against libjpeg that extracts images with two orders of magnitude more information than the page-fault channel attack.